2005
DOI: 10.1103/physrevb.72.125324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing parameters on the ferromagnetic properties of optimally passivated (Ga,Mn)As epilayers

Abstract: The influence of annealing parameters -temperature (Ta) and time (ta) -on the magnetic properties of As-capped (Ga,Mn)As epitaxial thin films have been investigated. The dependence of the transition temperature (TC) on ta marks out two regions. The TC peak behavior, characteristic of the first region, is more pronounced for thick samples, while for the second ('saturated') region the effect of ta is more pronounced for thin samples. A right choice of the passivation medium, growth conditions along with optimal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…3͑b͔͒ it is apparent that T Curie increases. 19 It remains basically unchanged for further annealing to 180 min, which is consistent with more extensive work presented by Stanciu et al 16 This enhancement of T Curie has been usually traced back to a removal of compensating defects, and thus, to an increase of the hole concentration. 17,20 In fact, channeling Rutherford backscattering 17 and Auger 20 experiments have shown that annealing at low temperature causes a migration of Mn interstitial defects towards the surface of GaMnAs.…”
supporting
confidence: 77%
“…3͑b͔͒ it is apparent that T Curie increases. 19 It remains basically unchanged for further annealing to 180 min, which is consistent with more extensive work presented by Stanciu et al 16 This enhancement of T Curie has been usually traced back to a removal of compensating defects, and thus, to an increase of the hole concentration. 17,20 In fact, channeling Rutherford backscattering 17 and Auger 20 experiments have shown that annealing at low temperature causes a migration of Mn interstitial defects towards the surface of GaMnAs.…”
supporting
confidence: 77%
“…• C for ten hours or longer reduces T C again [6,7,8], and annealing at higher temperatures leads to a more swift lowering of T C [8]. This twofold behavior clearly indicates that besides the Mn i out-diffusion another yet unknown microstructure evolution process takes place.…”
mentioning
confidence: 99%
“…Post-growth annealing of a few hours is an efficient method to remove the interstitial Mn i and thus increase T C [6,7,8,9]. However, extended annealing at temperatures around 250• C for ten hours or longer reduces T C again [6,7,8], and annealing at higher temperatures leads to a more swift lowering of T C [8]. This twofold behavior clearly indicates that besides the Mn i out-diffusion another yet unknown microstructure evolution process takes place.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In these configurations Mn is highly mobile [7] and tends to accumulate on the surface during crystal growth, resulting in non uniform doping profiles and Mn enriched surfaces. Thermal treatments on thin films in gaseous environment, or on As-capped samples [8], are used to remove Mn I thus improving the ferromagnetic properties of the material. These procedures causes Mn I to accumulate on the surface, in the form of a thick, non-magnetic layer.…”
Section: Introductionmentioning
confidence: 99%